Melodic Structures in the Double Jigs of O’Neill’s The Dance Music of Ireland: 1001 Gems (1907) - Doherty, Seán (Journal of the Society for Musicology in Ireland, 2022)
O’Neill’s The Dance Music of Ireland: 1001 Gems (1907) is a collection of foundational importance for the modern performance practice of Irish traditional music. This article examines the 365 double jigs of this collection in terms of their patterns of motivic repetition using an analytical methodology devised to explicate and compare the melodic structures of each part. This dataset demonstrates the prevalence of four standard melodic structures: period (39%), sentence (11%), hybrid (35%), and allied (2%). This survey considers the repetition of motives both within their originating part (internal repetition) and outside their originating part (external repetition) and shows that as the number of parts increases, so too does the amount of average overall repetition. These findings may provide a baseline to assess other tune classifications (reel, hornpipe, etc.), historical tune collections, regional repertoires, and the output of individual tune composers.